The mediating effect of entrepreneurs' competency on the relationship between bank finance and performance of micro, small, and medium enterprises (MSMEs) - Amare Abawa Esubalew; A. Raghurama (European Research on Management and Business Economics (ERMBE), 2020)
Entrepreneurial competencies are capabilities that the business mind people possess to create a new business idea or improve the existing one. Though the direct effect of entrepreneurs' competence on the performance of MSMEs was relatively researched, its mediating effect was not studied well. Therefore, the primary objective of this study was to investigate the mediating effect of the competence of entrepreneurs on the relationship between bank finance and performance of MSMEs and bridge the gaps in the literature. To meet the objectives, 411 MSMEs owner-managers were randomly selected. The Factor Analysis and Structural Equation Model (SEM) result revealed that the direct and mediating effect of entrepreneurs' competency was not significant. However, bank finance has a significant positive effect on the performance of MSMEs. Moreover, the study revealed the significant mediating effect of behavioral finance on the relationship between bank finance and performance of MSMEs. For entire variables used in the model, the mediation pattern shown was competitive mediation for bank finance and behavioral finance though it was nonmediation for bank finance and entrepreneurs' competency.
Keywords: L26; G21; L25; 650; Bank finance; Entrepreneur competency; Mediating effect; MSME performance